Resilient and Environmentally Efficient Residential Buildings - Assessment Method and Interim Outcomes. Issue 3 (November 2020) - Volf, M; Nehasil, O; Malík, Z; Hrabal, D; Růžička, J.; Lupíšek, A
Abstract: Historically, the fire-safety orders restricted the use of majority of the nature-based low impact materials in town buildings. Houses therefore became rigid and resilient. Today, we need to return to those materials, but the tradition and public opinion are preventing changes in building habits. This paper describes the work done within a research project, which aims to define a resilient and low impact residential building. The main goal of the research is a development of an assessment method that evaluates the building's ability to withstand or easily overcome most important threats which may occur in the Central European area. The research team's objective was to identify the risks, define the crisis scenarios and to provide an exemplary solution that will ensure the necessary resilience of a model building. The method includes environmental criteria with benchmarks set up to fulfil the requirements of the Paris Agreement. This leads the building design towards the low-impact materials and technologies and towards resilience at the same time. The research team developed an assessment method including 20 criteria. A set of buildings has been evaluated and favourable technical solutions have been developed. Based on the results, a design of a model building was carried out. New equipment and technologies were implemented: removable green facade, natural ventilation with solar chimneys, or a hybrid control system managing renewable sources in the building. The next step should be a test of the technology or the overall design in real conditions. The project outcomes show the possibility of reaching a sufficiently solid and robust design of a low-rise apartment building while following a sustainable design approach at the same time.